A Noninvasive Aid for Office-Based Gynecologists for the Diagnosis of Common External Genital Disorders - Giorgia Giuffrida; Francesco Lacarrubba; Simona Boscaglia; Maria Rita Nasca; Giuseppe Micali (Obstetrics and Gynecology International)
Background. Gynecology and dermatology share the diagnosis and the management of some disorders of the female external genital area. In the last decade, clinical diagnosis in dermatology has dramatically improved, thanks to the introduction of dermatoscopy. Technique. Dermatoscopy is a noninvasive, rapid, and simple technique performed with an affordable handheld instrument called dermatoscope, endowed with a light source and a high-quality lens achieving 10 times magnification. Experience. The use of dermatoscopy for the diagnosis of some common external genital disorders, i.e., genital warts (GW), vestibular papillomatosis (VP), molluscum contagiosum (MC), angiokeratoma (AK), and pediculosis pubis (PP), is presented and discussed. Conclusion. The use of dermatoscopy in a gynecologic office may considerably help the specialist to enhance in selected cases the clinical diagnosis and to avoid unnecessary and cumbersome investigations which may be time and money consuming.